Análisis de la técnica de williams vs. Estabilización segmental en la rehabilitación del adulto mayor con lumbalgia crónica producto de una osteoartrosis en la subsecretaría de Itagüí. (2006)
An investigation was made in the twelve people with chronic lumbalgia in the Subsecretaria de Itagüí, for analyze the effectivity of the technique Williams vs. Segmental Stabilization, doing this exercise during nine sessions of physiotherapy each sessions is about forty-five minutes, for do this the patients are divided in two group of six people and the evolutions with regard to the pain were registered daily. Between the mainly results was obtained that a seventy-three percent of the patients who did the exercise of Segmental Stabilization had a notorious improvement compared with a 33 percent of the patients who this the Williams.